The protection of migrant workers and their families in international human rights law. - Cholewinski, Ryszard I. (University of Ottawa (Canada), 1993)
This thesis focuses on the protection in international human rights law of the economic, social, cultural, political and residence rights of migrant workers and their families, broadly defined as long- or short-term immigrants who are or have been employed in countries other than their own, included those who entered illegally. These are the rights of most concern to migrants in the country of employment. Economic and social rights comprise employment rights, trade union rights and rights to social security, health, housing, family reunification and education. Cultural rights of migrants embrace their right to retain and develop cultural identity, including the teaching to their children of the culture and language of the country of origin, and political rights encompass their right to political activity and to participate in the decision-making process concerning their interests, including the right to vote. Residence rights comprise their right to remain in the host country, while in work and immediately after the termination of employment, and their rights to permanent residence and naturalization and to protection against unfair expulsion. The thesis develops a theoretical framework that is justified in terms of both individualist and communitarian liberal principales. These principles provide for conceptions of citizenship which go beyond mere form and which justify the extension of membership of the state to alien migrant workers and their families. These normative models also support the provision of more extensive rights to both legal and illegal migrants. Limiting the rights of migrants already in the territory and controlling the entry of new immigrants is justified by the principle of sovereignty on the basis of socio-economic, cultural and physical state security. This principal, however, is being eroded by the development of international standards for the protection of vulnerable groups. A redefined conception of the liberal-democratic community, which recognizes the participation and contribution of migrant workers and their families, is more responsive to the interdependence of the international community of states and more closely conforms to its own individualist and communitarian precepts. This thesis concludes with the conviction that the adequate realization of the rights of alien migrant workers and their families can only serve to advance the rights of all human beings, including citizen-members of states. (Abstract shortened by UMI.)
Keywords: Law.